International Doctoral Student Experience: Compassion, Connection, Commitment, and Creativity - Mao, Jing (Journal of International Students, 2022)
International doctoral students live with more uncertainty than most academic populations. In this essay, I attempt to provide a framework for living an international doctoral life by reflecting on my academic studies and personal living practices, drawing on van Lier’s (2008) notion of learner agency. Living a rhythm of life through compassion, connection, commitment, and creativity could holistically benefit the academic studies and wellbeing of international doctoral students.